2014
DOI: 10.1016/j.jvs.2013.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative transient ischemic attack on survival after carotid revascularization

Abstract: TIAs are significant events, possibly determined by a wider extent of atherosclerotic disease, with important effects on long-term mortality similar to that in strokes. Different from most trials evaluating the outcomes of revascularization techniques, the incidence of perioperative TIA should be accurately considered in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In the analysis of risk factors for CEA, the presence of SCI is rarely considered; we can only analyze other risk factors that can be indirectly associated with the presence of SCI such as previous cerebral symptoms and atrial fibrillation. 24,[34][35][36] Atrial fibrillation was more frequent in patients with SCI in our study. These patients may have an adjunctive risk, 24 either for the higher cardioembolic potential or for the risk of the anticoagulant therapy.…”
Section: Discussionsupporting
confidence: 50%
“…In the analysis of risk factors for CEA, the presence of SCI is rarely considered; we can only analyze other risk factors that can be indirectly associated with the presence of SCI such as previous cerebral symptoms and atrial fibrillation. 24,[34][35][36] Atrial fibrillation was more frequent in patients with SCI in our study. These patients may have an adjunctive risk, 24 either for the higher cardioembolic potential or for the risk of the anticoagulant therapy.…”
Section: Discussionsupporting
confidence: 50%
“…The incidence rate of TIA is in accordance with the stroke/death rate within 30 d. Recent studies have demonstrated that overall survival is significantly lower in patients with postoperative TIA, which is an independent predictor of decreased survival at the 5-year follow-up. 66 …”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical characteristics, technical aspects and perioperative (30-day) outcome were prospectively entered into a dedicated database in each of the two tertiary hospitals. As previously presorted, 13,14 the clinical characteristics included the following: age; sex; hypertension (presence of systolic blood pressure >140 or/and diastolic >90 mmHg, or specific therapy); dyslipidemia (total cholesterol >200 mg/dl or low density lipoprotein >120 mg/dl or specific therapy); diabetes mellitus (pre-diagnosed in therapy with oral hypoglycemic drugs or with insulin); current smoking; coronary artery disease (defined as a history of angina pectoris, myocardial infarction or coronary revascularization); chronic obstructive pulmonary disease (defined as chronic bronchitis or emphysema); chronic renal failure (glomerular filtration rate <60 ml/min); contralateral carotid occlusion and atrial fibrillation (paroxysmal or permanent). Perioperative medical therapy was also considered: specifically, single or double antiplatelet therapy, statins and oral anticoagulant therapy.…”
Section: Patient Selectionmentioning
confidence: 66%